2013
DOI: 10.4067/s0717-95022013000300018
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the Cement-Enamel Junction (CEJ), Clinical Correlations

Abstract: SUMMARY:The following study describes the mineralized tissue distribution which composes the cement-enamel junction, in a simple of Chilean people, comparing several teeth surfaces. Cervical area was observed (M-V, D-V, M-L/P, D-L/P sites) from 136 (n=68) longitudinal sections on premolars and incisors, with orthodontic or prosthetic reasons for exodontia, which were analyzed by optical microscope in order to identify the type of cement-enamel junction. For that measurement it was Choquet's criteria, founding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Many studies showed that defects in cementum or loss of cementum resulting in dentinal exposure would act as a contributing factor to pulpal inflammation and progression towards the need for a root canal treatment. Defects in cementum can arise during root surface debridement or can occur naturally as variations in the relationship between enamel and cementum at the cementoenamel junction [ 25 , 26 ]. An increase in the amount of bone loss does not necessarily lead to more non-vital teeth, which was confirmed in this study as there was no significant statistical relationship between the degree of bone loss and the percentage of teeth with RCT.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies showed that defects in cementum or loss of cementum resulting in dentinal exposure would act as a contributing factor to pulpal inflammation and progression towards the need for a root canal treatment. Defects in cementum can arise during root surface debridement or can occur naturally as variations in the relationship between enamel and cementum at the cementoenamel junction [ 25 , 26 ]. An increase in the amount of bone loss does not necessarily lead to more non-vital teeth, which was confirmed in this study as there was no significant statistical relationship between the degree of bone loss and the percentage of teeth with RCT.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, OM allows evaluating only 2 points of the CEJ of each sample, a fact that would allow greater errors of interpretation by generating optical illusions due to the thickness of the sections. 4,7,14,16,19 On the other hand, since there are studies that link the type of CEJ with the type of tooth and tooth sector, 14,16,25 it may be possible that, when studies are performed on teeth of different types, the results show great variability. However, some authors have concluded that, regardless of the type of method used, the type of CEJ of a tooth is unpredictable.…”
Section: Discussionmentioning
confidence: 99%
“…Roa et al (5) reported the four relationships between the cement and enamel that was described by Choquet in a sample of 68 teeth (9). In their findings, 51.9% of the cases described the relationship when the cement and enamel were in contact, whereas 42.4% of the cases showed that the enamel overlapped the cement.…”
Section: Discussionmentioning
confidence: 99%